N 4 S Bakery : tasty baking, healthy nation / Norazila Mustapha ... [et al.] - Mustapha, Norazila; Roslan, Shaiful Razif; Sheikh Ramli, Siti Noorzirah; Mohd Naser, Siti Nurazlina; Jumakun, Siti Zaharah (Faculty of Office Management & Technology, 2003)
Today, we can see food industry is one of the biggest economies activities. In our country, there are many bakery sells a cake, bread, pastry and other alternative of foods for people who cannot spend many times to eat because they have to complete their works. Our government has made policies and takes an action to being successful in any food activity. Thus make our company to take these advantages to build up this type of business.